Subsidies, Speed and Switching? Impacts of an Internet Subsidy in Colombia - Julian Hidalgo; Michelle Sovinsky (Review of Industrial Organization, 2025)
Inequality in access to health, education, and employment opportunities is exacerbated in developing nations due to the uneven distribution of access to high-speed internet connections. In Colombia, the government enacted a policy (in 2012) to subsidize internet fees for low-income households so as to bridge the digital divide. The reductions were not granted to all plans and thus created incentives for consumers to switch between plans. We estimate a structural model of demand for internet connection plans, which we use to quantify the importance of switching behavior. We estimate the model using data on plans that are offered by all internet service providers to households in all socioeconomic (SES) groups across Colombia. Our results indicate that the subsidy caused a non-negligible fraction of low-SES households to switch internet plans - the majority of which switched to plans with lower speeds, not higher speeds. Furthermore, the more wealthy households (of the lower SES groups) were twice as likely to switch plans than were those in the lowest SES group. Our findings suggest that the effect– not only on internet adoption but also on switching behavior– should be taken into account when formulating subsidies that are designed to bridge the digital divide.
Keywords: L15; L51; L86; D12; D31; 330; Digital divide; Internet access; Developing countries; Covid-19; Limited choice sets; Consumer switching behavior